2015
DOI: 10.1027/1015-5759/a000205
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Invariance of Oppositional Defiant Disorder Dimensions in 3-Year-Old Preschoolers

Abstract: Measurement invariance (metric/scalar) of oppositional defiant disorder (ODD) dimensions (negative affect, oppositional behavior, and antagonistic behavior) across sex and informants is tested. Parents and teachers of 622 preschool children from the general population answered a dimensional measure of ODD. ODD dimensions function similarly in boys and girls. Some differences were found by informant, indicating that the equivalence of the ratings of parents and teachers is not complete and that given the same u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Second, measurement invariance across type of facility, professional category and sex was performed following the common sequence explained previously (e.g., Vandenberg & Lance, ), by comparing progressively more constrained nested models across groups. For model identification, we used the factor‐variance strategy rather than the marker‐variable strategy (see, e.g., Byrne, ; Kim & Yoon, ); for the first step (configural model), this strategy consists of freely estimating all factor loadings and intercepts, whereas factor variances and latent means are fixed, respectively, at 1 and 0 in both groups (for more detailed model identification, see, for example, Ezpeleta & Penelo, ), preventing using as marker item that has not been proven to be noninvariant. For comparison between nested models, a decrease in CFI or TLI > .010 and an increase in RMSEA > .015 would indicate a meaningful decrement in fit and, therefore, noninvariance (Cheung & Rensvold, ).…”
Section: Methodsmentioning
confidence: 99%
“…Second, measurement invariance across type of facility, professional category and sex was performed following the common sequence explained previously (e.g., Vandenberg & Lance, ), by comparing progressively more constrained nested models across groups. For model identification, we used the factor‐variance strategy rather than the marker‐variable strategy (see, e.g., Byrne, ; Kim & Yoon, ); for the first step (configural model), this strategy consists of freely estimating all factor loadings and intercepts, whereas factor variances and latent means are fixed, respectively, at 1 and 0 in both groups (for more detailed model identification, see, for example, Ezpeleta & Penelo, ), preventing using as marker item that has not been proven to be noninvariant. For comparison between nested models, a decrease in CFI or TLI > .010 and an increase in RMSEA > .015 would indicate a meaningful decrement in fit and, therefore, noninvariance (Cheung & Rensvold, ).…”
Section: Methodsmentioning
confidence: 99%
“…This assesses how well items of a scale correlate with each other. The average internal consistency of irritability scales is high (α = 0.75), 19 , 37 , 40 , 49 , 50 , 51 , 52 , 53 ranging from 0.49 (for ad hoc − created scales) 19 to 0.92 (for specifically developed irritability scales). 50 …”
Section: Reliabilitymentioning
confidence: 99%
“…Measurement invariance has been supported across maternal and paternal ratings of ODD behaviours (Burns et al., ). Measurement invariance across parent and teacher reports has been explored in preschool children (Ezpeleta & Penelo, ). This study found a consistent factor structure in parent and teacher report in terms of loading pattern (configural invariance) and magnitude (metric invariance) in a three‐factor model.…”
Section: Introductionmentioning
confidence: 99%